Tetrahydrobiopterin and alkylglycerol monooxygenase substantially alter the murine macrophage lipidome. - Watschinger, K; Keller, M; McNeill, E; Alam, M; Lai, S; Sailer, S; Rauch, V; Patel, J; Hermetter, A; Golderer, G; Geley, S; Werner-Felmayer, G; et al. (National Academy of Sciences, 2015)
Tetrahydrobiopterin is a cofactor synthesized from GTP with well-known roles in enzymatic nitric oxide synthesis and aromatic amino acid hydroxylation. It is used to treat mild forms of phenylketonuria. Less is known about the role of tetrahydrobiopterin in lipid metabolism, although it is essential for irreversible ether lipid cleavage by alkylglycerol monooxygenase. Here we found intracellular alkylglycerol monooxygenase activity to be an important regulator of alkylglycerol metabolism in intact murine RAW264.7 macrophage-like cells. Alkylglycerol monooxygenase was expressed and active also in primary mouse bone marrow-derived monocytes and "alternatively activated" M2 macrophages obtained by interleukin 4 treatment, but almost missing in M1 macrophages obtained by IFN-γ and lipopolysaccharide treatment. The cellular lipidome of RAW264.7 was markedly changed in a parallel way by modulation of alkylglycerol monooxygenase expression and of tetrahydrobiopterin biosynthesis affecting not only various ether lipid species upstream of alkylglycerol monooxygenase but also other more complex lipids including glycosylated ceramides and cardiolipins, which have no direct connection to ether lipid pathways. Alkylglycerol monooxygenase activity manipulation modulated the IFN-γ/lipopolysaccharide-induced expression of inducible nitric oxide synthase, interleukin-1β, and interleukin 1 receptor antagonist but not transforming growth factor β1, suggesting that alkylglycerol monooxygenase activity affects IFN-γ/lipopolysaccharide signaling. Our results demonstrate a central role of tetrahydrobiopterin and alkylglycerol monooxygenase in ether lipid metabolism of murine macrophages and reveal that alteration of alkylglycerol monooxygenase activity has a profound impact on the lipidome also beyond the class of ether lipids.